Total Ankle Arthroplasty Historical Overview, Current Concepts and Future Perspectives - Hintermann, Beat.; SpringerLink (Online service) (Vienna : Springer Vienna, 2005)
Increasing success of arthroplasty of joints like the hip and knee along with concerns about the long-term outcomes of ankle arthrodesis has renewed interest in ankle arthroplasty. The new implants have been designed with attention to reproducing normal ankle anatomy, joint kinematics, ligament stability, and mechanical alignment. This publication will be the first comprehensive atlas on this topic and offers a unique physiological and mechanical characteristics of the ankle joint and of the selected total ankle system. Furthermore it will greatly enhance one$1 (Bs knowledge of this dynamic field and stimulate the scientific approach to management of end-stage arthritis of the ankle. It reflects the author$1 (Bs accumulated experience of the last decade with extended laboratory work on biomechanics of the ankle joint complex and more than 350 total ankle procedures. The atlas is well illustrated with many impressive figures, drawings and coloured pictures.s
Characteristics of the Diseased Ankle -- Ankle Arthrodesis -- Anatomic and Biomechanical Characteristics of the Ankle Joint and Total Ankle Arthroplasty -- History of Total Ankle Arthroplasty -- Current Designs of Total Ankle Prostheses -- Preoperative Considerations for Total Ankle Arthroplasty -- Surgical Techniques -- Postoperative Care and Follow-Up -- What is Feasible in Total Ankle Arthroplasty? -- Complications of Total Ankle Arthroplasty -- Future Directions.
Keywords: Medicine; Orthopedics; Surgery; Thoracic surgery; Medicine & Public Health; Surgical Orthopedics; Orthopedics; Surgery; Thoracic Surgery; Electronic books